COVID-19 and the failure of pharmaceutical innovation for the global South: The example of "neglected diseases" and emerging infectious diseases - Werner G. Raza (Austrian Foundation for Development Research (ÖFSE), 2021)
The debate about the lack of access to COVID-19 vaccines for the countries of the Global South joins a long history of struggle for effective and affordable treatments for those several dozen diseases for which the World Health Organisation (WHO) uses the telling adjective "neglected". Empirical evidence shows that the pharmaceutical innovation system, built over the last thirty years around the global protection of so-called intellectual property rights (IPR), has failed across the board in providing treatments for these diseases. The same applies to the category of new infectious diseases, which also includes coronaviruses. Here, too, there has been little research and development effort, even though the dangers of the diseases they cause had been known for 20 years. The COVID-19 pandemic should therefore be used for a fundamental reform with the aim of aligning pharmaceutical innovation more closely with public health goals. In addition to a stronger financial commitment from the EU, the pharmaceutical industry should also be required to make a greater contribution to the fight against these diseases, for example in the form of a levy to fund research and development (R&D) for "neglected diseases" and new infectious diseases.
Keywords: 330; TRIPS-agreement; COVID-19; neglected diseases; new infectious diseases; patents